Epistemological Approach of Listening Method in Memorizing Juz Amma in Madrasah Ibtidaiyah - Kusniah, Siti (International Proceedings of Nusantara Raya, 2024)
In the era of globalization that is full of information and challenges, the role of madrasah as an Islamic educational institution is increasingly strategic. One of the important aspects that must be mastered by madrasah students is the science of religion and the deepening of the Qur'an. This study aims to analyze philosophically the implementation of listening methods in the process of memorizing Juz Amma in Madrasah Ibtidaiyah. Through an epistemological approach, this study explores how the knowledge of the Qur'an, especially Juz Amma, is constructed in the minds of children through the process of listening repeatedly. The study also discusses the philosophical implications of this method on students ' understanding of the meanings and values contained in the Qur'an. The results of the study are expected to contribute to the development of a more effective and meaningful method of learning the Qur'an. This study seeks to integrate the theories of educational philosophy with the practice of learning to memorize Juz Amma in Madrasah Ibtidaiyah. The study analyzes how the listening method, which is one of the popular learning methods, can be philosophically justified. In addition, this study also evaluates the effectiveness of this method in achieving the goals of Islamic education, which is to form a generation of faith, piety, and noble character.